New fossils of Gaindatherium (Rhinocerotidae, Mammalia) from the Middle Miocene of Pakistan - Khan, Abdul Majid (2014)
New isolated teeth with maxillary and mandibular fragments from the Chinji Formation of the Lower Siwaliks are described and determined as Gaindatherium browni and Gaindatherium vidali. This material comes from the Middle Miocene of Lava and Dhok Bun Ameer Khatoon localities, northern Pakistan, and significantly increases the number of remains previously known for this rhinocerotid genus. Specimens from the Lava site determined as G. vidali present morphological differences with respect to those of G. browni, being similar to those of G. vidali from the Nagri Formation, showing a greater size. Previously, G. vidali was reported only from the Nagri Formation of the Middle Siwaliks and the new material thus significantly widens the chronological distribution of this species in the continental deposits of the Siwaliks. This record implies that both species are not successive but rather coeval during the late Middle Miocene.